Heavy Metal Pollution and Phytoremediation- A Review - Gautam, Sabita; Paudel, Mukti Ram; Devkota, Anjana (Nepal Journal of Botany, 2025)
Heavy metal pollution is a critical environmental issue driven by industrialization and urbanization. These pollutants persist in the environment, posing risks to soil, plants, and human health due to their toxicity, non-biodegradability, and bioaccumulation potential. Metals like lead, cadmium, arsenic, and mercury disrupt soil microbial activity, impair nutrient cycling, and cause physiological damage to plants, including stunted growth, chlorosis, and reduced photosynthesis. In humans, heavy metal exposure leads to serious health issues, such as organ damage, developmental disorders, and increased cancer risks. Traditional remediation techniques are often costly and disruptive, emphasizing the need for sustainable alternatives. Phytoremediation, an innovative and eco-friendly approach, uses plants to absorb, store, and neutralize heavy metals from contaminated soil, water, and air. Various techniques, including phytoextraction, rhizofiltration, phytostabilization, and phytovolatilization, use plants to remove or control contaminants, providing natural solutions for cleaning and protecting the environment. Hyperaccumulator plants such as Thlaspi caerulescens, Alyssum murale, Pteris vittata etc play a major role in efficiently absorbing and neutralizing toxic metals to restore contaminated environments. Despite challenges like slow remediation rates, plant toxicity, and the variability of metal uptake across species, advancements in biotechnology and the identification of resilient plant species help to increase the effectiveness of phytoremediation. Therefore, phytoremediation as a sustainable and cost-effective method has great potential for mitigating heavy metal pollution and restoring contaminated environments.